Perancangan Standard Operating Procedure (SOP) Pemeliharaan Sarana Proteksi Kebakaran pada Sekolah Dasar Net Zero Carbon (NZC) - Rivaldo Bimo Oktaviano Agustinus Putra; Hans Dermawan (Universitas Batanghari Jambi, 2026)
The high incidence of fire emergencies in Indonesian elementary schools and the limited availability of maintenance guidelines for fire protection systems pose significant safety risks, particularly in Net Zero Carbon (NZC) schools equipped with photovoltaic systems. This situation is exacerbated by the absence of a comprehensive and structured maintenance Standard Operating Procedure (SOP) in NZC elementary schools. This study aims to design an SOP for maintaining fire protection systems that is aligned with the operational characteristics and specific needs of NZC elementary schools. A descriptive quantitative approach was employed, with data collected through questionnaires and analyzed using the probability index and matrix method based on the PMBOK 6th edition risk management framework to identify and prioritize potential risks. The results indicate five dominant high-level risks, namely the absence of an SOP for fire protection (0.34), the lack of a regular inspection schedule (0.28), the absence of maintenance records (0.21), irregular inspection of solar panels (0.20), and the lack of dedicated maintenance personnel (0.18). These findings formed the basis for developing a maintenance SOP that includes daily, monthly, and periodic inspection procedures, integrating solar panel assessment to prevent fire-related hazards. In conclusion, the proposed SOP provides a preventive, measurable, and accountable framework for maintenance activities, and has the potential to enhance the effectiveness of fire protection systems in NZC elementary schools on a sustainable basis.